Simulated impacts of climate change on Lake Simcoe water quality. Issue 2 (3rd April 2022) - Bolkhari, Hadiseh; Boegman, Leon; Smith, Ralph E. H.
ABSTRACT: Lake Simcoe has undergone eutrophication and hypoxia since the 1960s. Climate change, leading to enhanced summer thermal stratification, has been identified as a key stressor. In this study, we modeled the impacts of climate change on hydrodynamics and biogeochemistry in Lake Simcoe by applying a 1-dimensional (vertical) model forced with A2 and B1 scenario outputs from a global climate model over 2000–2100. The model was calibrated in 2008 and validated in 2009, with maximum root mean square error (RMSE) of modelled temperature between 1.5 and 3.0 °C and dissolved oxygen RMSE between 0.5 and 2.5 mg L −1 . Phytoplankton chlorophyll a was simulated with RMSE between 1.25 µg L −1 (large diatoms) and ∼0.5 µg L −1 (other groups). Interannual variability in spring water temperature and length of stratification were related to changes in the North Atlantic and Artic Oscillation indices, respectively. Under A2 and B1 forcing, the duration of stratification will increase by 45 and 38 days in summer between spring and fall turnover, respectively. The extended stratified period leads to a reduction in hypolimnetic dissolved oxygen from 3–7 to <3 mg L −1, thereby reducing the quality of cold-water fish habitat and increasing internal phosphorus loading from the benthos. These internal loads, combined with increased water temperatures, lead to increased cyanobacteria concentrations, beginning around 2070.